-2(7+5b)+3(2b-3)=

Simple and best practice solution for -2(7+5b)+3(2b-3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(7+5b)+3(2b-3)= equation:


-2(7+5b)+3(2b-3)=0

We simplify the equation to the form, which is simple to understand
-2(7+5b)+3(2b-3)=0

Reorder the terms in parentheses
+(-14-10b)+3*(2b-3)=0

Remove unnecessary parentheses
-14-10b+3+*(+2b-3+)=0

Reorder the terms in parentheses
-14-10b+(+6b-9)=0

Remove unnecessary parentheses
-14-10b+6b-9=0

We move all terms containing b to the left and all other terms to the right.
-10b+6b=0+14+9

We simplify left and right side of the equation.
-4b=+23

We divide both sides of the equation by -4 to get b.
b=-5.75

See similar equations:

| 2x+x-11+-7x=15 | | -136-8x=170-36x | | G(x)=-x^2-19x-18 | | -12m+8=-13m | | 19=7m+5(3-m) | | 2x-45=6 | | w^2=x+v^2 | | 7(6x+2)= | | x^2-45=20 | | (6c-5)+8(3c+4)= | | 12(3x+6)= | | -2(-2)(-3)(-4)-5= | | 6g=24-2(3+3g) | | 313+n=400 | | 5(h-2)-(3-2h)= | | 7=8x-5y | | 2(4x+9)= | | 2x+11=52-3x | | 4f*2+3f*(-2)= | | -13x+1=-90 | | 7x-7y=-5 | | -2(11b-3)= | | 5(9x+5)= | | -83=15x+7 | | 8x+2=91 | | 80=-8x+8 | | -8=-17x+26 | | 15a=10 | | 14x/2= | | 5c+34=-2(1-7c) | | x-7=2(4x-3) | | i-(-3)=9 |

Equations solver categories